Remediation of Manganese-Contaminated Coal-Mine Water Using Bio-Sorption and Bio-Oxidation by the Microalga Pediastrum duplex (AARLG060): A Laboratory-Scale Feasibility Study - Thongpitak, Jakkapong; Pekkoh, Jeeraporn; Pumas, Chayakorn (Frontiers in Microbiology, 2019)
Acidification occurs as a result of acid mine drainage after the oxidative weathering of metal sulfides. The acidic condition corrodes other toxic elements from the soil and becomes distributed around the operating site. Although coal mines go through a process of rehabilitation, water samples in the rehabilitated reservoir still reveal high concentrations of certain metals, for example, manganese (Mn). Both living and non-living biomass substances were used in Mn remediation. However, using non-living biomass as a sorbent may be inappropriate for the purposes of upscaling in high-volume water bodies. Thus, living microalga, Pediastrum duplex AARLG060, has become of significant interest for this type of application. The Mn remediation of microalga was performed by biosorption and bio-oxidation. The aim of this study was to evaluate the potential of microalgal Mn remediation of the water obtained from a rehabilitated coal-mine reservoir. The equilibrium and isotherm values of the remediation process were also studied. The microalga was used to remediate Mn in water under three different water conditions, including filtrated water obtained from the rehabilitated site, non-filtrated water that was sterilized with an autoclave, and non-treated water. Remediation was performed by culturing microalga with modified medium consisting of N P C and Mg nutrients. The remediated Mn concentration present in the cultures was detected by atomic absorption spectroscopy. The precipitated Mn was collected as a result of bio-oxidation, and EDTA was used to wash Mn from the biomass. This was designated as an adsorption result. Characterization of biosorption was evaluated by employing the Langmuir and Freundlich models. The results demonstrated that all treatments of living microalga could support Mn bio-oxidation. The Mn remediation was successfully performed at over 97% in every treatment. The adsorption characteristics revealed a close similarity to the Langmuir isotherm of monolayer adsorption. The SEM-EDS indicated precipitation of Mn oxide on the cell surface, while TEM revealed that the nanoparticles of Mn were scattered mainly in the chloroplast and throughout the vacuoles of the cells.